Collective Trademark as an Alternative to Shared Trademark Protection for Micro, Small and Medium Enterprises in Indonesia - Nugroho, Samuel Adhi; Afianti, Arifana Ismir; Indirayani, Nisa Qodrea; Hutauruk, Kezia Elisabeth; Permatasari, Talyta Putri (Fakultas Hukum, Universitas Diponegoro, 2022)
Collective trademark regulation and collective trademark registration procedures in Indonesia are an important part of the legal framework that seeks to protect and promote groups of producers or service providers belonging to associations or similar groups. At the regulatory level, Indonesia has issued Trademark Law No. 20 of 2016 which includes provisions regarding Collective Trademarks. The collective trademark registration procedure involves applying to the Directorate General of Intellectual Property (DJHKI) and complying with the requirements set by the regulations. However, there are several disadvantages to this system. The use of Collective Trademarks has been identified as a potential tool to protect and advance Micro, Small and Medium Enterprises (MSMEs) in Indonesia. A collective mark is a type of trademark used by members of a group or association of manufacturers or service providers to identify products or services manufactured or provided by members of that group. Along with rapid economic growth and increased competition in the market, MSMEs in Indonesia face major challenges in protecting their trademarks. This article investigates the legal framework governing Collective Trademarks in Indonesia, and identifies weaknesses.Keywords: Trademark, Business, Indonesia